Believing in a Purpose of Events: Cross‐Cultural Evidence of Confusions in Core Knowledge. Issue 3 (21st January 2014) - Barber, Justin
Summary We examined beliefs in the purpose of events in the American population. Previously, separate researchers surveyed these beliefs in the Finnish population. Their methodology was used to assess the beliefs in a dissimilar demographic. Four hypotheses were tested using questionnaire responses (N = 429; 301 women; Mage = 20.46) and analyzed with structural equation modeling. As hypothesized, a positive correlation was found between beliefs in the purpose of events and paranormal beliefs. Confusions of core biological, physical, and psychological knowledge predicted the belief variables—as hypothesized, although model fit was mediocre. Core knowledge confusions were also hypothesized to predict religiousness and purposeful‐event beliefs. A close‐fitting model displayed weak predictive power and was interpreted as insufficient support for the third hypothesis. Lastly, we hypothesized and found that participants rated events they experienced as more purposeful than events that they did not experience. We provide insight for the findings and make suggestions for future studies. Copyright © 2014 John Wiley & Sons, Ltd.